Bystander Intervention Behavior as Function of Victimization History, Opportunity, and Situational Context - Woods, William C. (Journal of interpersonal violence, 2022)
Preliminary research has demonstrated the utility of bystander interventions in reducing sexual assault, and initial research has begun extending this type of intervention to intimate partner violence more broadly. However, the extant research is limited by methodological issues that fail to examine opportunity for intervention relative to intervention behaviors as well as a failure to examine intervention rates across differing risk situations. Further, there are many unexplored factors that may impact bystander intervention behavior, notably previous experiences with intimate partner violence and sexual assault. Thus, the current study examined bystander opportunities and intervention across situations of varying risk to the bystander, as well as the relationship of opportunity/intervention relative to victimization history. Given the rates of sexual assault and IPV on college and university campuses, the research examined the number of times college students (N = 393) encountered a range of situations in which bystander intervention may be indicated, and their intervention behavior across varying risk levels to the bystander. Results demonstrated that individuals with a history of psychological victimization were more likely to intervene across all situation types, but sexual and physical victimization provided mixed support for hypotheses. No differences in witnessing or intervening were found as a function of gender. These results replicate previous findings, and further provide evidence for a more nuanced approach to examine bystander behavior intervention. Implications and directions for future research are discussed.